Factors Affecting Health Literacy as Related to Asthma and COPD Management: Learning from Patient and Health Care Professional Viewpoints - Iris van der Heide; Iraj Poureslami; Jessica Shum; Roger Goldstein; Samir Gupta; Shawn Aaron; Kim L. Lavoie; Claude Poirier; J. Mark FitzGerald (SLACK Incorporated, 2021)
Background: Studies have identified health literacy (HL) as an important determinant of asthma and chronic obstructive pulmonary disease (COPD) management. There are, however, limited data on patients' and health care professionals (HCPs') insights about the link between HL and management of asthma and COPD. Objective: The aim of this study was to elicit patients' and HCPs' perspectives with respect to factors affecting HL in the context of asthma and COPD management. Methods: A total of 16 semi-structured focus groups (10 in English and 6 in French) with patients with asthma or COPD (n = 93) and 45 interviews with HCPs, researchers, and policymakers were conducted between June 2015 and April 2017. Participants were asked to share their perspectives with respect to five predefined HL domains-accessing, understanding, evaluating, communicating, and using health-related information-in relation to disease self-management practices. Data were analyzed qualitatively, using a content analysis approach. Key Results: Most patients and HCPs reflected on factors hampering HL in relation to asthma and COPD management. Thoughts such as "not having enough time during medical consultations," "not receiving consistent messages from different health care professionals," and "language or cultural differences" were frequently mentioned by both patients and HCPs. Conclusions: We identified multiple factors affecting communication between patients and HCPs as it relates to the self-management of their disease. These included inconsistent messages from different providers, limited consultation time, use of technical language, failure to account for cultural differences, and reduced health literacy, especially as it related to written communication. Future interventions that aim to enhance HL skills in the context of asthma and COPD self-management should consider these issues. [HLRP: Health Literacy Research and Practice. 2021;5(3):e179-e193.] Plain Language Summary: The current study advances the health literacy (HL) knowledge base by adding patients' and health care professionals' valuable insights on factors that hamper or facilitate HL in relation to asthma and chronic obstructive pulmonary disease (COPD) management. An important insight from this study is that receiving conflicting information from different health care professional's hampers HL in patients with asthma and/or COPD.